Kształtowanie nowej tożsamości bibliotekarza w erze zmian technologicznych i mobilności usług bibliotecznych - Karwasińska, Emilia; Karwasiński, Piotr (My University, 2013)
Artykuł stanowi analizę zmian zachodzących w bibliotekarstwie pod wpływem wdrażania innowacji technologicznych i postawy bibliotekarzy wobec zagrożeń wynikających z naruszenia stabilizacji zawodowej. Czy biblioteka może sobie pozwolić na zatrudnianie pracowników cyfrowo wykluczonych? Czy mniejsza liczba czytelników w czytelniach to wyłącznie zagrożenie? Jak przez Twittera i Facebooka „nie rozmienić się na drobne”? Omówiona została rola i znaczenie bibliotekarza wdrożeniowca, konsultanta i tutora. Ich niestereotypowe zadania skupiają się na projektowaniu, przygotowaniu, administracji i obsłudze elektronicznych usług komunikacyjnych, szkoleniowych oraz tych zapewniających innowacyjne korzystanie z biblioteki wirtualnej. Czy biblioteki są gotowe i rzeczywiście szeroko otwarte na erę mobilności?

This paper presents an analysis of the changes currently taking place in librarianship that have been effected by the implementation of innovative IT technologies and the changes in librarians’ attitudes towards threats (risks) stemming from the resulting instability in the profession. Can a library afford to take on staff members that are digitally disqualified? Is the decreasing number of readers in reading rooms the only threat to the library? How not to get side-tracked into minor issues by the extensive use of Twitter and Facebook? During the presentation, the role and significance of the librarian implementing innovative technologies as well as the consultant and the tutor will be discussed. It is their non-conventional tasks focusing on designing, preparation, administration and handling of electronic services that facilitate communication, training and provide innovative use of virtual libraries. Are libraries ready enough for the change and are they really open wide to accept the new era of mobility?
Shaping a new image and identity of the librarian in the wake of technological changes and the development of further mobility of library services
Artykuł zostanie opublikowany w monografii z II Międzynarodowej Konferencji Naukowej „Biblioteka w przestrzeni edukacyjnej. Bibliotekarz 2.0 - nowoczesność na bazie tradycji”, 23-24 maja Kraków.
Keywords: biblioteki akademickie; academic libraries; rola bibliotekarza; librarian roles; usługi elektroniczne; electronic services; usługi w chmurze; cloud computing; virtual reference; komunikacja zdalna